Implementasi Kurikulum 2013 oleh Guru Pendidikan Agama Islam pada Sekolah Dasar di Samarinda - Jumali, Jumali (Pascasarjana Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2014)
This study aims to determine how the implementation of the 2013 curriculum by Islamic religious education teachers in elementary schools (SD) in Samarinda. This research is qualitative research and the point of research is in the second semester of Elementary School (SD) in Samarinda City academic year 2013/2014. The data sources used are the Islamic religious teachers in elementary school in Samarinda. The sampling technique used was purposive sampling and snowball sampling. Data collection techniques used is observation, interviews, and documentation. Testing the validity of the data include a test of credibility, transferability, dependability, and conformability. Data analysis techniques used is data reduction, data presentation, and verification.The result of the study shows that the implementation of the 2013 curriculum by Islamic religious teachers in elementary schools in Samarinda, Some of them is still not implementing the standardized processes optimally. Particularly, in the form of teaching planning administration. The problem is the lack of training 2013 curriculum, the lack of technology mastery, too much students, evaluation, and describing value for report cards, lack of cooperation between parents and teachers, the limitations of PAI books in 2013 curriculum.The results of this study concluded that the implementation of the 2013 curriculum by Islamic religious teachers in elementary schools (SD) in Samarinda is not done well and there are too much less optimal in practice.